ДОСЛІДЖЕННЯ НОВОГО СПОСОБУ КУВАННЯ ВЕЛИКИХ ЗЛИТКІВ НА ОСНОВІ ОСАДЖЕННЯ ПРОФІЛЬОВАНИХ ЗАГОТОВОК - Марков, Олег; Хващинський, Антон; Мусорін, Антон; Маркова, Марина; Лисенко, Антон (Технічні науки та технології, 2022)
Quantity of massive parts produced from an ingot is increasing today. It is caused by increasing in the capacity of a massive equipment. However, the quality of produced forging parts does not corresponds to customer`s requirements. Poor quality of the produced forging parts is caused by low quality of forging ingots. Defects of ultrasonic test after forging of the massive forging parts equal to 10%. The defects after ultrasonic test are caused by upsetting operation of the ingots with no equal internal structure. As a result, this structure is processed unevenly and insufficiently. Increasing of the ingot internal defects occurs during upsetting operation of billets by flat deformation tools. The purpose of this work is establishing the rational geometry of billets with conical faces which guarantee the uniform distribution of the deformations, and significant hydrostatic stresses. Analysis of the strain and stress states allows find that in the billet at the upsetting operation occurs the state with nonuniform compress stresses. Raising the degree of the compressive stresses in the internal and external parts can be obtained after upsetting of the shot billets (H/D<3.0). Raising the deformation degree from till 0.45 provides to letdown factor of the stress state η from –1,0 to 0. The upsetting till 0.7 raises this factor to +1.5. It was established that decreasing diameter of the conical faces leads to reduction the factor η. This factor has a more significant influence for welding of the internal cavities in the –1.5...–0.6 at upsetting operation with the comparative diameter of the conical faces of the 0.5. Upsetting of the toll billets leads to the reduction degree of logarithmic strains and reduction equability of the localization. Obtained geometrical parameters of the billets with conical faces are able to be introduced in producing of the massive forged parts.